Seroprevalence of Trypanosoma cruzi in kidney transplant donors and recipients in Mexico City. Issue 6 (1st August 2013) - Rodríguez‐Romo, R.; Morales‐Buenrostro, L.E.; Reyes, P.A.; Gracida, C.; Medeiros, M.; Mancilla, E.; De Leo, C.; Alberú, J.
Abstract Infectious diseases are common causes of morbidity and mortality among kidney transplant recipients. Chagas disease (CD) has been recognized as an emerging infectious complication of transplantation caused by the parasite Trypanosoma cruzi. CD is prevalent in Mexico, particularly in the southern coastal region. The impact on Mexican kidney transplant programs has not been previously studied prospectively. From 2009 through 2010, serum samples from 59 kidney transplant donors and 405 renal transplant recipients were screened for antibodies against T. cruzi. Serum was initially screened using a locally developed ELISA test; positive results were confirmed by an indirect immunofluorescense test, in accordance with Panamerican Health Organization/World Health Organization guidelines. None of the donors were seropositive for T. cruzi, while 8 (1.97%) kidney transplant recipients were confirmed to be seropositive for T. cruzi. None of them have developed clinical manifestations of CD, although specific screening of recipients was not performed. A prospective study is planned to define the epidemiology and outcome of CD among kidney transplant donors and recipients in Mexico more thoroughly.